Beyond Disclosure: Does Sustainability Control Maturity Drive Eco-Efficiency in State-Owned Enterprises? - Andi Iswoyo; Rodhiyah Rodhiyah; Endah Supeni Purwaningsih; Pramandyah Fitah Kusuma; Salsabila Azka Az-Zahra (Universitas Hayam Wuruk Perbanas, 2026)
This study examines whether Sustainability Management Control System Maturity (SMCSM) is associated with eco-efficiency in Indonesian non-financial state-owned enterprises. Using annual reports and sustainability reports from 33 enterprises over the 2015–2024 period, this study develops a report-based SMCSM index covering sustainability target setting, KPI measurement, monitoring and evaluation, managerial accountability and governance, corrective action and learning, and integration with operational and risk control. The full dataset contains 320 firm-year observations, whereas the main energy model uses 90 observations from 12 firms due to uneven availability of environmental data. Eco-efficiency is measured using revenue-based environmental efficiency indicators, with energy eco-efficiency as the main dependent variable and emission and water eco-efficiency as robustness measures. The empirical analysis employs panel regression with firm fixed effects and clustered standard errors. The results do not support a significant association between SMCSM and energy eco-efficiency, and similar patterns appear in lagged models, sensitivity tests, and robustness models using emission and water eco-efficiency. However, changes in the scope of environmental reporting are consistently associated with energy eco-efficiency, indicating that the reporting boundary and measurement coverage affect the comparability of report-based environmental performance. This study contributes to sustainability management accounting by introducing a documentary SMCSM index and highlighting the importance of the reporting scope for interpreting eco-efficiency data. Practically, the findings suggest that managers and regulators should not treat disclosed sustainability control maturity as direct evidence of environmental efficiency improvement unless reporting boundaries and operational embedding are clearly established.